Dynamometer use for sarcopenia and mayor clinical event valuation - Balmaceda Araya, Ernesto (2023)
Sarcopenia is a muscle disease that tends to be related to aging. However, it plays an extremely relevant role in the clinic of chronic pathologies. This role is quantified by clinical tests such as the dynamometer, allowing to establish an association between the loss of muscle mass, the general condition and the prognosis of patients with different pathologies. The pathophysiology of sarcopenia centers on a decrease in anabolic hormone signaling and an increase in catabolic signaling through proinflammatory substances such as tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6). A loss of skeletal muscle function, strength and mass is generated, which favors the development of chronic diseases. This has a negative impact on aspects such as quality of life, patient survival, increased risk of fractures, increased cardiovascular complications, increased post-transplant complications and generally increased hospitalization and mortality rates. This pathology has a great relevance in the prognosis of patients with chronic diseases. An early study and detection of sarcopenia can have a significant impact on therapeutic decisions, disease progression and patient outcomes.